Climate change related processes affecting mountaineering itineraries, mapping and application to the Valais Alps (Switzerland). Issue 2 (3rd April 2022) - Mourey, Jacques; Ravanel, Ludovic; Lambiel, Christophe
ABSTRACT: Climate change leads to deep modifications of high Alpine environments. Those modifications have significant consequences on mountaineering itineraries and make them technically more difficult and more dangerous. Although a growing number of studies have recently documented this issue, they only list the processes affecting the itineraries and do not document their characteristics. Therefore, the acquired data lack relevance to be spread and for prevention making among climbers. In the present study, on the basis of the processes identified in previous studies in the Mont Blanc massif, we developed a legend in order to map the processes related to climate change that affect the itineraries and modify their climbing parameters. Following the UNIL geomorphological legend and using the same color code, 21 symbols were defined to map 23 processes. In order to evaluate the applicability and interest of the legend proposed, we present a first application in the Valais Alps (Switzerland), based on 21 semi-structured interviews with local Alpine guides and hut keepers. The map then allowed to list the processes affecting each of the 36 itineraries studied. On average, an itinerary is affected by 9 different processes and 25% of the itineraries have greatly evolved, which means their ascent in summer cannot be recommended anymore because of climate change. More generally, this legend would provide a common methodological basis, destined to be completed within future studies and to be relevant beyond the European Alps. This basis would also ease the comparability and compilation of results from different future studies.